Phytochemical compounds in sport nutrition: Synephrine and hydroxycitric acid (HCA) as examples for evaluation of possible health risks. Issue 6 (2nd May 2017) - Bakhiya, Nadiya; Ziegenhagen, Rainer; Hirsch‐Ernst, Karen I.; Dusemund, Birgit; Richter, Klaus; Schultrich, Katharina; Pevny, Sophie; Schäfer, Bernd; Lampen, Alfonso
Abstract : Numerous food supplements that are marketed for athletes and physically active people contain phytochemical compounds as active ingredients. Having the aura of being natural, such supplements are often perceived by consumers as being risk‐free. However, in many cases the safety of marketed herbal food supplements is currently uncertain, particularly for those products that have not undergone a premarket review or approval procedure. The present review provides two examples for risk assessment for phytochemical ingredients that are used in certain sports supplements—for synephrine and for hydroxycitric acid. Within this scope, the evidence from animal studies and clinical trials on the safety of synephrine and hydroxycitric acid is critically assessed. Furthermore, the current challenges regarding risk assessment of phytochemical supplements are discussed. Abstract : Numerous food supplements contain phytochemical compounds as active ingredients. Although such supplements are often perceived by consumers as being risk‐free, the safety of many of them is currently uncertain. The present review provides two examples for risk assessment for phytochemical ingredients that are used in certain supplements marketed for sportspeople—synephrine (extracted from fruits of Citrus aurantium ) and hydroxycitric acid (HCA, isolated from fruits of Garcinia cambogia ). Animal and human studies, as well as case reports, provide evidence for cardiovascular effects due to ingestion of high synephrine doses, especially in combination with caffeine and physical exertion. A dose of up to 6.7 mg synephrine/day, however, which is equivalent to the median dietary intake from conventional foods in Germany, is presumed to represent a safe intake from supplements. In subchronic animal studies, administration of high doses of certain HCA‐containing preparations led to testicular toxicity (i.e., testicular atrophy and impaired spermatogenesis), yielding a no observed adverse effect level of 389 mg HCA/kg bw/day. In view of lack of adequate human data on the safety of HCA preparations, particularly with respect to the human male reproductive system, substantial uncertainties exist regarding the safety of supplements containing high amounts of HCA.